A Profile of the Academy of Management Member: Reply - Forsgren, Roderick A. (Academy of Management Journal, 1970)
The article reports the author's opinions regarding a critique of his article ?A Profile of the Academy of Management Member.? The author focuses on comparing the data he has collected regarding members of the Academy of Management to that obtained by W. Jack Duncan. It is recommended that the Academy of Management consider active solicitation to boost membership.